The derived process of derivational morpheme found in “the power of a positive wife book” - Sumariani, Ni Putu; Winarta, Ida Bagus Gde Nova; Putra, I Gusti Bagus Wahyu Nugraha (Journal of Language and Applied Linguistics, 2020)
The purpose of the research is to describe the derived process of derivational morpheme found in “The Power of a Positive Wife Book” This study focused on: The derived process of each derivational morpheme used in “The Power of a Positive Wife Book.” Qualitative and supported by quantitative method was used in this research and the data source was “The Power of a Positive Wife” Book. The method used in collecting the data was descriptive qualitative method. The result of the analysis was presented by using formal and informal method. In affixes, have three types as follows: suffix, infix and prefix. The total data of derivational morpheme found in The Power of a Positive Wife Book was 195 words.